PERFORMANSI MOTOR BAKAR 6 TAK DENGAN 2 KALI PEMBAKARAN MENGGUNAKAN BAHAN BAKAR PERTAMAX DAN ETANOL - Elandi; Eko Siswanto; Agung Sugeng Widodo (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2021)
The six-stroke combustion engine is a refinement of the four-stroke engine by adding 2 steps from the four-stroke combustion engine. The 2 steps in question are the second compression stroke and the second expansion stroke, so in one work cycle, there are 2 compressions and 2 combustions. The method used is a direct experimental research method by testing the intended object. Based on previous research, different fuels affect performance (torque, power, and fuel consumption). This study aims to obtain the performance value of Pertamax and Ethanol fuel in a six-stroke engine, the fuel used is Pertamax fuel with a purity of 100% and Ethanol with a purity of 99.7%. Based on the research, analysis, and discussion results, the performance of a six-stroke combustion engine with 2 combustions using Pertamax and Ethanol fuels concluded that the maximum torque using Pertamax fuel is 8.15 N.m at 7200 rpm engine speed. For comparison, Ethanol fuel is 6.59 N.m at 7200 rpm engine speed, the average torque of Pertamax fuel is 1.16% higher than Ethanol fuel. Maximum power for Pertamax fuel is 8.25 HP at 7200 rpm engine speed. For comparison, Ethanol fuel is 6.67 HP at 7200 rpm engine speed.